MAGNESIUM DEFICIENCY IN CHILD NEUROLOGY: WHAT SHOULD A PAEDIATRICIAN KNOW? - G. А. Karkashadze; L. S. Namazova-Baranova; A. M. Mamed'yarov; Т. А. Konstantinidi; N. S. Sergienko ("Paediatrician" Publishers LLC, 2014)
Deficiency of micronutrients in a diet of the modern children increases risk of the formation of chronic neurologic and somatic pathology. Magnesium deficiency, which initiates a various neurologic symptomatology, has a particular importance in the progress of nervous system diseases at children. Diagnosis of neurologic manifestations of a micronutrient deficiency requires comprehension of the main mechanisms of their development, and also peculiarities of laboratory diagnostics. In treatment of consequences of a magnesium deficiency the special role belongs to the micronutrient stock replacement (medication, alimentary) combined with traditional methods of treatment of neurologic disorders.